Novel Protocol for Estimating Viruses Specifically Infecting the Marine Planktonic Diatoms - Yuji Tomaru; Kei Kimura (Diversity, 2020)
Since their discovery, at least 15 diatom viruses have been isolated and characterised using a culture method with two cycles of extinction dilution. However, the method is time consuming and laborious, and it isolates only the most dominant virus in a water sample. Recent studies have suggested inter-species host specificity of diatom viruses. Here, we describe a new protocol to estimate previously unrecognised host-virus relationships. Host cell cultures after inoculation of natural sediment pore water samples were obtained before complete lysis. The proliferated viral genomes in the host cells were amplified using degenerate primer pairs targeting protein replication regions of single-stranded RNA (ssRNA) and single-stranded DNA (ssDNA) viruses, and then sequenced. Diverse ssRNA virus types within known diatom virus group were detected from inoculated Chaetoceros tenuissimus and C. setoensis cells. A previously unknown ssDNA virus type was detected in inoculated C. tenuissimus cells, but not in C. setoensis cells. Despite the possible protocol biases, for example non-specific adsorptions of virions onto the host cells, the present method helps to estimate the viruses infectious to a single host species. Further improvements to this protocol targeting the proliferated viral genomes might reveal unexpected diatom–virus ecological relationships.